A10.14 Inhibition of sclerostin accelerates TNFα-mediated bone destruction. (24th February 2016) - Wehmeyer, C; Frank, S; Beckmann, D; Böttcher, M; Cromme, C; König, U; Fennen, M; Held, A; Paruzel, P; Hartmann, C; Stratis, A; Korb-Pap, A; et al.
Abstract : Background and objectives: Wnt-inhibitor sclerostin has anti-anabolic effects on bone formation by negatively regulating osteoblast differentiation. Loss of sclerostin expression results in high bone mass and bone strength in patients with sclerosteosis and sclerostin knockout mice. Therefore, antibody-mediated inhibition of sclerostin is currently evaluated for the treatment of osteoporosis in humans. Since it has been shown that sclerostin is upregulated by TNFα, we studied its impacton inflammatory arthritis using RA mouse models such as the human TNF transgenic (hTNFtg) model, the G6PI-induced arthritis model and the K/BxN serum transfer-induced arthritis model. Materials and methods: Sclerostin knockout ( sost -/- ) mice were crossed with hTNFtg mice to generate sost -/ - /hTNFtg. Mice with serum transfer-induced arthritis were generated by injection of arthritogenic serum collected from K/BxN mice in sost -/- and wild type (WT) mice. Arthritis was induced in DEREG mice by immunisation with recombinant glucose-6-phosphate isomerase (G6PI). To switch to the non-remitting G6PI-induced arthritis, Foxp3 + regulatory T-cells were depleted by diphtheria toxin. hTNFtg and G6PI-induced arthritis mice were treated with a neutralising antibody against human and murine sclerostin. Clinical disease severity, bone erosion, cartilage destruction and pannus formation were evaluated by histomorphometric, x-ray and micro-CT analysis. Sclerostin expression and p38 activation was assessed by immunohistochemistry, western-blot-analysisor RT-PCR. Knockdown of LRP5 and LRP6 was performed by transfection of fibroblast-like synoviocytes (FLS) with siRNA. Results: This study showed for the first time that TNFα induces sclerostin expressionin RA-FLS. Surprisingly, the lack of sclerostin and its antibody-mediated inhibition led to deterioration of RA-like disease in hTNFtgmice with enhanced pannus formation and joint destruction. Suggesting a specific role for sclerostin in TNFα signalling, inhibition of sclerostin also failed to improve clinical signs and joint destruction in the partially TNFα-dependent G6PI-induced arthritis, but ameliorated disease severity in K/BxN serum transfer-induced arthritis, in which TNFα plays only a minor role. FLS from sost -/- /hTNFtg mice displayed increased TNFα-mediated p38 activation, a key step in arthritis development. In turn, sclerostin effectively blocked TNFα-induced but not IL-1-induced activation of p38 with participation of the canonical Wnt receptor LRP6. Conclusion: Collectively, these data demonstrated that sclerostin appears to have a protective function in TNF-mediated chronic inflammation.